Detection of Host Vertebrate DNA in Tick Species Collected from Vegetation in Fukuoka, Japan - Kobayashi, Takayuki; Ashizuka, Yuki (Japanese journal of infectious diseases, 2025)
Ticks are the vectors of tick-borne diseases (TBDs) in humans and wild vertebrates. The relationship between ticks, host vertebrates, and their pathogens should be investigated for effective control of TBDs. This study aimed to detect vertebrate DNA in ticks using molecular methods and identify the species of ticks collected in Fukuoka Prefecture, which is located in the northern Kyushu area of Japan. Ticks from vegetation were collected from the vegetation by flagging between 2017 and 2023. Of the 152 ticks collected by flagging, 65 (42.8%) harbored vertebrate DNA. By stage, vertebrate DNAs were detected in 26 of 83 nymphs (31.3%) and 39 of 69 adults (56.5%). Among the host vertebrates, Sika deer was the main blood-feeding source for ticks in Fukuoka Prefecture. Owing to the widespread of deer across this prefecture, controlling its population and other wildlife populations could be a countermeasure to reduce the TBD risk.